The Effect of Bacterial Adhesion on Grafted Chains Revealed by the Non-Invasive Sum Frequency Generation Spectroscopy. Issue 5 (11th July 2012) - Bulard Bulard, Emilie Emilie; Fontaine-Aupart Fontaine-Aupart, Marie-Pierre Marie-Pierre; Dubost Dubost, Henri Henri; Zheng Zheng, Wanquan Wanquan; Herry Herry, Jean-Marie Jean-Marie; Bellon-Fontaine Bellon-Fontaine, Marie-Noëlle Marie-Noëlle; Briandet Briandet, Romain Romain; Bourguignon Bourguignon, Bernard Bernard
Abstract : In biomedical and food industry, surface colonization by bacteria is harmful: it leads to biofilm formation, a microbial consortia more resistant to antibiotics than planktonic bacteria. In order to design materials able to limit the biofilm formation, the effect of bacteria on materials has to be well characterized. In this work, a well-defined surface composed of a self-assembled monolayer (SAM) of octadecanethiol (ODT) onto a gold surface is probed in situ . The SAM conformation is obtained using the femtosecond vibrational sum frequency generation (SFG) spectroscopy. This technique provides selectively the molecular vibrational signature of the interface. The behaviour of the ODT SAM is studied in different environments: in air, in water, and upon exposure to hydrophilic or hydrophobic Lactococcus lactis bacteria. Modelling the experimental SFG spectra reveals a measurable change of the SAM conformation which depends on the environment, especially on the hydrophilic-hydrophobic character.